Porous cellulose and method for producing same
Patent Information
- Application Number
- JP2021535423
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-01
- Filing Date
- 2020-07-30
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-07-30
AI Technical Summary
【0009】 本開示によれば、無置換のセルロースにより構成された多孔質セルロースそのものにはない機能性が付与された、新規な多孔質セルロースを提供することができる。
Abstract
Description
[Technical field]
[0001] The present disclosure relates to porous cellulose and a method for producing the same. [Background technology]
[0002] Polysaccharides, such as cellulose, and their derivatives are used in a variety of applications. For example, these microporous materials can themselves act as adsorbents, and their surfaces can be chemically modified to provide them with functions such as adsorption, separation, and catalysis.
[0003] For example, various methods for producing matrices for biopolymer separation using cellulose, agarose, etc. have been disclosed, and their usefulness is well known. In order to give functionality to the surfaces of cellulose and other polysaccharides, chemical modification is performed. For example, when the -OH group of a sugar is reacted with chloroacetic acid under basic conditions, carboxymethyl ether is produced, and when it is reacted with 1-chloro-2-(diethylamino)ethane, diethylaminoethyl ether is produced, and both are used as weak ion exchangers. However, such chemical modification not only increases costs, but may also have a negative effect on the micro- to macro-structure of the particles. For this reason, a simpler method for introducing functional groups is desired.
[0004] On the other hand, as a method for producing cellulose beads, for example, Patent Document 1 discloses a method in which cellulose is dissolved in an aqueous alkali hydroxide solution containing urea or thiourea, and the solution is sprayed and brought into contact with a coagulating liquid. Also, for example, Patent Document 2 discloses a method in which cellulose is finely dispersed in an alkali hydroxide solution, which is then dispersed in an organic liquid and brought into contact with a coagulating liquid. These are excellent methods for obtaining cellulose beads having micropores by simple processes, but there are problems as mentioned above when chemically modifying them. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-133355 A [Patent Document 2] International Publication No. 2015 / 046473 Summary of the Invention [Problem to be solved by the invention]
[0006] A primary object of the present disclosure is to provide a novel porous cellulose that is endowed with functionality not found in porous cellulose composed of unsubstituted cellulose itself, and a method for producing the same. [Means for solving the problem]
[0007] The inventors of the present disclosure have conducted intensive research to solve the above problems. As a result, they have adopted a method for producing porous cellulose comprising a step of preparing a mixed solution containing a polymer having a glucose unit other than unsubstituted cellulose and unsubstituted cellulose, and a step of contacting the mixed solution with a coagulation solvent, and have found that a novel porous cellulose having functionality not found in porous cellulose itself composed of unsubstituted cellulose can be obtained by setting the content of the polymer in the mixed solution to 20% by mass or less in a total of 100% by mass of the polymer and unsubstituted cellulose. The present disclosure has been completed based on these findings and through further research.
[0008] Item 1. A polymer having a glucose unit other than unsubstituted cellulose, Unsubstituted cellulose; A porous cellulose comprising: The porous cellulose has a content of the polymer of 20% by mass or less relative to 100% by mass of the total of the polymer and unsubstituted cellulose. Item 2. The porous cellulose according to item 1, wherein the solid content of the porous cellulose in a water-containing state, as measured by the following method, is 10 mass % or less. (Method for measuring solid content) The porous cellulose in the state of being precipitated in the pure water is left to stand for one day or more in an environment at atmospheric pressure and at a temperature of 25°C. Next, about 2 mL of the porous cellulose in the pure water is sucked up with a pipette, dispersed in 20 mL of a solution in which a neutral detergent is diluted 1000 times with pure water, and left to stand for one day or more to allow the porous cellulose to settle. Then, the supernatant is removed by decanting, and about 1 / 3 of the remaining slurry is dropped onto a filter paper equivalent to the three types specified in JIS P 3801 [filter paper (for chemical analysis)] as one sample, and left for 20 seconds to remove excess moisture, and then the mass of the porous cellulose remaining on the filter paper is peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose. Next, the porous cellulose is dried in an oven at 80°C for two hours and then weighed to obtain the dry mass. These operations are performed on three samples, and the ratio of the dry mass to the wet mass is calculated for each sample, and the average of the three values obtained is obtained as the solid content. Item 3. The porous cellulose according to Item 1 or 2, wherein the polymer is a cellulose derivative. Item 4. The porous cellulose according to Item 3, wherein the cellulose derivative is at least one selected from the group consisting of carboxymethyl cellulose, carboxyethyl cellulose, cellulose phosphate, cellulose sulfate, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, N,N-diethylaminoethyl cellulose, and N,N-dimethylaminoethyl cellulose. Item 5. The porous cellulose according to any one of Items 1 to 4, wherein the porous cellulose has a particle, monolith, or membrane shape. Item 6. A step of preparing a mixed solution containing a polymer having a glucose unit other than unsubstituted cellulose and unsubstituted cellulose; contacting the mixed solution with a coagulation solvent; Equipped with The method for producing porous cellulose, wherein in the mixed solution, the content of the polymer is 30 mass% or less based on a total of 100 mass% of the polymer and the unsubstituted cellulose. Item 7. The method for producing porous cellulose according to Item 6, wherein in the step of preparing the mixed solution, the polymer and the unsubstituted cellulose are dissolved in a solvent to prepare the mixed solution. Item 8. The method for producing porous cellulose according to Item 7, wherein in the step of preparing the mixed solution, the polymer and the unsubstituted cellulose are dissolved in the solvent simultaneously or sequentially to prepare the mixed solution. Item 9. The method for producing porous cellulose according to Item 6, wherein in the step of preparing the mixed solution, the polymer solution and the unsubstituted cellulose solution are mixed to prepare the mixed solution. Item 10. The method for producing porous cellulose according to any one of Items 6 to 9, wherein the polymer is a cellulose derivative. Item 11. The method for producing porous cellulose according to Item 10, wherein the cellulose derivative is at least one selected from the group consisting of carboxymethyl cellulose, carboxyethyl cellulose, cellulose phosphate, cellulose sulfate, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, N,N-diethylaminoethyl cellulose, and N,N-dimethylaminoethyl cellulose. Item 12. The method for producing porous cellulose according to any one of Items 6 to 11, wherein the step of contacting the mixed solution with the coagulation solvent is a step of converting the mixed solution into microdroplets in a gas and then absorbing the microdroplets into the coagulation solvent. Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a novel porous cellulose that is endowed with functionality not present in porous cellulose composed of unsubstituted cellulose. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The porous cellulose of the present disclosure is a porous cellulose containing a polymer having glucose units, excluding unsubstituted cellulose, and unsubstituted cellulose, and is characterized in that the content of the polymer is 20% by mass or less in the total of 100% by mass of the polymer and unsubstituted cellulose. The porous cellulose of the present disclosure has such a configuration, and thus is endowed with functionality that is not present in the porous cellulose itself that is composed of unsubstituted cellulose (i.e., functionality that the polymer has, particularly functionality based on the functional group that the polymer has).
[0011] Furthermore, as described above, the porous cellulose of the present disclosure that exhibits such functionality can be suitably produced by employing a method for producing porous cellulose that includes the steps of preparing a mixed solution containing unsubstituted cellulose and a polymer having a glucose unit excluding unsubstituted cellulose, and contacting the mixed solution with a coagulation solvent, and by setting the content of the polymer in the mixed solution to 20% by mass or less out of a total of 100% by mass of the polymer and unsubstituted cellulose.
[0012] The porous cellulose and the method for producing the same according to the present disclosure will be described in detail below.
[0013] 1.Porous cellulose The porous cellulose of the present disclosure includes a polymer having a glucose unit excluding unsubstituted cellulose, and unsubstituted cellulose (hereinafter sometimes simply referred to as "unsubstituted cellulose").
[0014] In the present disclosure, unsubstituted cellulose means that the hydroxyl groups of cellulose are not substantially substituted (i.e., it is not a substituted cellulose), and is, for example, cellulose with a degree of hydroxyl substitution of 0.05 or less.
[0015] In the present disclosure, a polymer having a glucose unit other than unsubstituted cellulose is a polymer having a glucose unit, but different from unsubstituted cellulose (hereinafter, may be referred to simply as "polymer"). In the present disclosure, the polymer contained in the porous cellulose has a glucose unit, and therefore has a high affinity with the unsubstituted cellulose contained together with the polymer, and is homogeneously dispersed in the unsubstituted cellulose in the porous cellulose, thereby forming a stable porous cellulose. As a result, a novel porous cellulose is obtained that is endowed with functionality not present in porous cellulose composed only of unsubstituted cellulose.
[0016] That is, in the present disclosure, a polymer having the glucose unit (a polymer formed by dehydration condensation of glucose, i.e., a polymer containing glucans and its derivatives, like unsubstituted cellulose) is used as a blend polymer contained together with unsubstituted cellulose. Note that there are multiple dehydration condensation forms of glucose, and the dehydration condensation form in the polymer is not particularly limited. Below, a typical example of the dehydration condensation form of glucose is exemplified. Dehydration condensation is a form in which dehydration is performed exclusively from the hydroxyl group at the 1st position of glucose and the hydroxyl group other than the 1st position of the condensation partner glucose. At this time, there are two possible stereochemistry at the 1st position, α and β. On the other hand, the hydroxyl groups at the 2nd, 3rd, 4th, and 6th positions can be condensed as condensation partners, but each of these has a fixed stereochemistry. Therefore, there are no two epimers like the 1st position. In principle, all combinations of α and β at the 1st position and the 2nd to 6th positions of the other partner are possible, and there are also cases in which the same polymer has multiple different bond patterns. Representative glucans include cellulose with β-1,4-bonds (however, in this disclosure, unsubstituted cellulose is excluded), amylose with α-1,4-bonds, dextran with α-1,6-bonds, pullulan with a mixture of α-1,4-bonds and α-1,6-bonds, curdlan with β-1,3-bonds, schizophyllan with glucose bonded as a side chain, α-1,3-bonds, etc. The names exemplified here are often used exclusively by specific microorganisms or plants that produce them, but the present disclosure is not necessarily limited to those with these names.
[0017] As the polymer, a cellulose derivative is preferred since it has a polarity and a main chain shape similar to those of unsubstituted cellulose.
[0018] In addition, examples of the substituents (functional groups) possessed by cellulose derivatives include substituents bonded via ester bonds, such as sulfate groups, phosphate groups, and acetate groups; and substituents bonded via ether bonds, such as methyl groups, ethyl groups, hydroxyethyl groups, carboxymethyl groups, and carboxyethyl groups.
[0019] In the porous cellulose of the present disclosure, from the viewpoint of particularly suitably exhibiting functionality not found in the porous cellulose itself composed only of unsubstituted cellulose, specific examples of preferred polymers include carboxymethyl cellulose, carboxyethyl cellulose, cellulose phosphate, cellulose sulfate, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, N,N-dimethylaminoethyl cellulose, and N,N-diethylaminoethyl cellulose (DEAE cellulose). These polymers have a cellulose skeleton similar to unsubstituted cellulose, so that it is easy to select a cosolvent with unsubstituted cellulose, and they are easily retained in the porous cellulose, so they are particularly preferred. The polymer contained in the porous cellulose of the present disclosure may be one type, or two or more types.
[0020] The degree of polymerization of the polymer is not particularly limited, but from the viewpoint of increasing the affinity with the unsubstituted cellulose in the porous cellulose and suitably exerting the functionality not found in the porous cellulose composed only of the unsubstituted cellulose, it is, for example, 10 or more, preferably 100 or more. The upper limit of the degree of polymerization of the polymer is, for example, 1000 or less, and the preferred range of the degree of polymerization of the polymer is about 10 to 500, more preferably about 100 to 300. As described later, the degree of polymerization of the unsubstituted cellulose is not particularly limited, but is preferably, for example, 1000 or less. If the degree of polymerization is 1000 or less, the dispersibility and swelling in an alkaline aqueous solution described later will be high, which is preferable. If the degree of polymerization of the unsubstituted cellulose is 10 or more, the mechanical strength of the obtained porous cellulose will be high, which is preferable. The preferred range of the degree of polymerization of the unsubstituted cellulose is about 100 to 500.
[0021] In the porous cellulose of the present disclosure, the polymer content is 20% by mass or less, where the total of the polymer and the unsubstituted cellulose is 100% by mass. In the present disclosure, since the polymer content is set to 20% by mass, the porous cellulose exhibits gel properties in water while retaining the porous structure formed by the unsubstituted cellulose, and furthermore, the polymer is retained in the porous cellulose, thereby enabling the porous cellulose to exhibit functionality that is not present in the porous cellulose itself that is composed only of the unsubstituted cellulose. From the viewpoint of more suitably exerting these properties, the upper limit of the polymer content is preferably 15 mass% or less, more preferably 10 mass% or less, and even more preferably 8 mass% or less, and the lower limit is preferably 1 mass% or more, more preferably 2 mass% or more, and even more preferably 3 mass% or more. Preferred ranges include about 1 to 20 mass%, about 1 to 15 mass%, about 1 to 10 mass%, about 1 to 8 mass%, about 2 to 20 mass%, about 2 to 15 mass%, about 2 to 10 mass%, about 2 to 8 mass%, about 3 to 20 mass%, about 3 to 15 mass%, about 3 to 10 mass%, and about 3 to 8 mass%.
[0022] The porous cellulose of the present disclosure is preferably obtained in a state dispersed or immersed in water, as described below. The porous cellulose of the present disclosure is in a hydrated state in water and forms a hydrous gel. The porous cellulose of the present disclosure can be stored in a normal water-wet state. The porous cellulose of the present disclosure preferably has a solid content of 10% by mass or less in a hydrated state, as measured by the following method. The lower limit of the solid content is, for example, 1% by mass or more, preferably 3% by mass or more, and the preferred range is 1 to 10% by mass, or 3 to 10% by mass.
[0023] (Measurement of solid content) The porous cellulose that has settled in the pure water is left to stand for at least one day (usually within three days) in an environment at atmospheric pressure and a temperature of 25° C. Next, about 2 mL of the porous cellulose in the pure water is sucked up with a pipette, dispersed in 20 mL of a solution in which a neutral detergent (for example, Mama Lemon, a product of Lion Corporation) is diluted 1000 times with pure water, and left to stand for at least one day (usually within three days) to settle. The supernatant is then removed by decantation, and 1 / 3 of the remaining slurry is dropped onto a filter paper (e.g., No. 131 150 mm, manufactured by ADVANTEC Co., Ltd.) corresponding to the three types specified in JIS P 3801 [filter paper (for chemical analysis)] as one sample, left for 20 seconds to remove excess moisture, and then the porous cellulose lump remaining on the filter paper is peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose (if the porous cellulose is in a lump form, a lump of approximately 200 to 300 mg is cut out, the excess moisture attached to the surface is absorbed by rolling it on the filter paper, and then weighed, dried, and weighed again). Next, the porous cellulose is dried in an oven at 80°C for 2 hours to obtain the dry mass. These operations are performed on three samples, and the ratio of the dry mass to the wet mass is calculated for each sample, and the average of the three values obtained is taken as the solid content.
[0024] When the porous cellulose of the present disclosure is stored for a long period of time in a wet state, a preservative such as alcohol or sodium azide is added to prevent spoilage. Also, the cellulose may be dried, preferably freeze-dried, after adding glycerin, sugar, urea, or the like.
[0025] The shape of the porous cellulose of the present disclosure is not particularly limited, and examples thereof include particles (spherical particles, irregular particles), lumps (monoliths), membranes, etc. For example, when the shape of the porous cellulose of the present disclosure is particles, the particle size of the porous cellulose particles can be appropriately selected depending on the application, with the lower limit being, for example, 1 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, and 50 μm or more, and the upper limit being, for example, 3 mm or less, 600 μm or less, 500 μm or less, 400 μm or less, and 300 μm or less, with preferred ranges being about 1 to 600 μm, about 1 to 500 μm. , about 1 to 400 μm, about 1 to 300 μm, about 5 to 600 μm, about 5 to 500 μm, about 5 to 400 μm, about 5 to 300 μm, about 10 to 600 μm, about 10 to 500 μm, about 10 to 400 μm, about 10 to 300 μm, about 20 to 600 μm, about 20 to 500 μm, about 20 to 400 μm, about 20 to 300 μm, about 50 to 600 μm, about 50 to 500 μm, about 50 to 400 μm, and about 50 to 300 μm. These particle sizes are particularly suitable when the porous cellulose of the present disclosure is used as a filler or carrier for chromatography. When the porous cellulose particles of the present disclosure are actually used, further classification is performed depending on the purpose, and a more suitable particle size range is used. For example, when the porous cellulose of the present disclosure has a monolithic shape, the size of the porous cellulose monolith may be appropriately selected depending on the application (for example, when used as a chromatography carrier, the size may be adjusted to match the size of a column). For example, when the porous cellulose of the present disclosure has a membrane shape, the thickness of the porous cellulose membrane may be appropriately selected depending on the application (for example, a hollow fiber membrane, etc.), and may be, for example, about 100 μm to 5 mm.
[0026] In addition, the porous cellulose of the present disclosure exhibits functionality not found in porous cellulose composed solely of unsubstituted cellulose, and can therefore be suitably used, for example, in size exclusion chromatography. This also means that the cellulose can be used in various chromatographic separation modes other than size exclusion. These include ion exchange, hydrophobic, affinity, and other modes.
[0027] Furthermore, the porous cellulose of the present disclosure can be used as a separating agent with improved strength by covalently cross-linking cellulose chains using a cross-linking agent.
[0028] Affinity ligands can also be immobilized on the porous cellulose and crosslinked porous cellulose media of the present disclosure to produce adsorbents, which can also be used as separation materials for affinity chromatography.
[0029] In the present disclosure, the method for producing porous cellulose is not particularly limited, so long as it produces the porous cellulose of the present disclosure having the above-mentioned configuration, and the porous cellulose can be suitably produced by the production method shown in "2. Production method for porous cellulose" below.
[0030] 2. Method for producing porous cellulose The method for producing porous cellulose of the present disclosure includes a step of preparing a mixed solution containing a polymer having a glucose unit other than unsubstituted cellulose and unsubstituted cellulose (mixed solution preparation step), and a step of contacting the mixed solution with a coagulation solvent (coagulation step). In addition, in the mixed solution, the polymer content is 30% by mass or less in a total of 100% by mass of the polymer and unsubstituted cellulose. Details of the polymer and unsubstituted cellulose are as described in the above section "1. Porous Cellulose". The reason for setting the upper limit of the polymer content in the mixed solution to 30% by mass or less, which is higher than the upper limit of the polymer content in the porous cellulose described above of 20% by mass or less, is that the polymer may be somewhat leached out when forming a gel in the coagulation step. It is also possible to produce porous cellulose with the aforementioned polymer content of more than 20% by mass and 30% by mass or less by using the method for producing porous cellulose of the present disclosure.
[0031] (Mixed solution preparation process) The mixed solution preparation step is a step of preparing a mixed solution containing a polymer having a glucose unit other than unsubstituted cellulose and unsubstituted cellulose. In the mixed solution preparation step, as long as a mixed solution containing a polymer and unsubstituted cellulose at a predetermined content is prepared, there is no particular limitation on the preparation method. For example, in the mixed solution preparation step, a polymer and unsubstituted cellulose are dissolved in a solvent to prepare a mixed solution. More specifically, in the mixed solution preparation step, a method of simultaneously or sequentially dissolving a polymer and unsubstituted cellulose in a solvent to prepare a mixed solution, and a method of mixing a polymer solution (hereinafter sometimes referred to as a "polymer solution") and a solution of unsubstituted cellulose (hereinafter sometimes referred to as a "unsubstituted cellulose solution") to prepare a mixed solution can be mentioned.
[0032] When a method is adopted in which a polymer and unsubstituted cellulose are dissolved in a solvent simultaneously or sequentially to prepare a mixed solution, a solvent capable of dissolving both the polymer and the unsubstituted cellulose is selected to prepare the mixed solution.
[0033] On the other hand, in the method of preparing a mixed solution by mixing a polymer solution and an unsubstituted cellulose solution, a polymer solution is prepared using a solvent capable of dissolving a polymer, and an unsubstituted cellulose solution is prepared using a solvent capable of dissolving unsubstituted cellulose, and these solutions are mixed to prepare a mixed solution. The solvent capable of dissolving a polymer and the solvent capable of dissolving unsubstituted cellulose may be the same or different, but since it is not preferable that precipitation occurs when the polymer solution and the unsubstituted cellulose solution are mixed, it is preferable to use the same solvent as the solvent for these solutions. Even if the same solvent is used, if the solutes are different, they may not be easily mixed, but if the mixing ratio of the two solutions is biased to one side, it can be said that even if phase separation occurs in part immediately after mixing, it often becomes one phase in the end.
[0034] In the unsubstituted cellulose solution, polymer solution, and mixed solution, examples of the solvent include copper ethylenediamine solution, N-methylmorpholine oxide (NMMO) monohydrate, an aqueous alkali hydroxide solution, a caustic alkali-urea aqueous solution, an aqueous calcium thiocyanate solution, an N,N'-dimethylacetamide solution of lithium chloride or lithium bromide, a dimethylformamide solution of lithium chloride, a dimethylimidazolium solution of lithium chloride, a dimethylsulfoxide solution of lithium chloride, and an ionic solvent mainly composed of an alkylimidazolium salt. Only one of these solvents may be used, or two or more of them may be mixed and used. As the solvent, an aqueous liquid (a liquid mainly composed of water) is preferable, and among these, an aqueous alkali hydroxide solution and an aqueous alkali hydroxide-urea aqueous solution (for example, an aqueous urea-alkali hydroxide solution containing urea, thiourea, etc.) are particularly preferable.
[0035] A specific example of the aqueous liquid as the solvent is a 7 to 10 mass % aqueous solution of an alkali hydroxide (alkali hydroxide aqueous solution), preferably an aqueous solution further containing 5 to 15 mass % of urea or thiourea (urea-alkali hydroxide aqueous solution). As the alkali hydroxide, lithium hydroxide and sodium hydroxide are preferred in terms of the solubility of unsubstituted cellulose and polymers, and sodium hydroxide is preferred in terms of raw material cost. In the case of a solvent based on this alkali hydroxide aqueous solution, the solute (unsubstituted cellulose, polymer) and the solvent are cooled to about -10°C to -15°C, preferably while stirring, and then the operation of returning to room temperature is carried out once or several times, to obtain a fluid solution. Furthermore, if insoluble matter remains and adversely affects the function of the final product, the insoluble matter can be removed by filtration or centrifugation. It can also be dissolved in a 40 to 60 mass % aqueous solution of lithium bromide heated to 100°C or higher. When the organic solvent is mainly used, for example, the above-mentioned lithium chloride or N,N'-dimethylacetamide containing 8 to 12 mass % of lithium bromide is preferred. However, the above-mentioned aqueous sodium hydroxide solution or aqueous urea-alkali hydroxide solution is a more preferable solvent because it is inexpensive and has a smaller environmental impact in that it does not leave behind any harmful substances if properly neutralized.
[0036] The term "unsubstituted cellulose solution" refers to a liquid containing unsubstituted cellulose, which shows fluidity and solidifies in a state in which the unsubstituted cellulose and the polymer are compatible when the unsubstituted cellulose solution is mixed with a polymer solution and comes into contact with a coagulation solvent. It does not matter whether the unsubstituted cellulose molecules are dispersed in the unsubstituted cellulose solution, whether some associations remain, or whether fine fibrous materials are simply dispersed (sometimes called a dispersion). That is, in the method for producing porous cellulose of the present disclosure, the unsubstituted cellulose solution means a liquid containing unsubstituted cellulose, and is a concept that includes a dispersion in which unsubstituted cellulose is dispersed in a liquid and a solution in which unsubstituted cellulose is dissolved in a liquid. In the method for producing porous cellulose of the present disclosure, when preparing the unsubstituted cellulose solution, it is sufficient that the unsubstituted cellulose solution contains unsubstituted cellulose, and the form of the unsubstituted cellulose may be any of a dispersion, a dissolution, or a mixture thereof.
[0037] The same applies to the polymer solution, which refers to a liquid containing a polymer, which exhibits fluidity and solidifies in a state in which the unsubstituted cellulose and the polymer are compatible with each other when the polymer solution comes into contact with a coagulation solvent as a mixed solution mixed with the unsubstituted cellulose solution, and whether the polymer molecules are dispersed in the polymer solution, whether some associations remain, or whether fine fibrous materials are simply dispersed (sometimes called a dispersion). That is, in the method for producing porous cellulose of the present disclosure, the polymer solution means a liquid containing a polymer, and is a concept that includes a dispersion in which a polymer is dispersed in a liquid and a solution in which a polymer is dissolved in a liquid. In the method for producing porous cellulose of the present disclosure, when preparing a polymer solution, it is sufficient that the polymer solution contains a polymer, and the form of the polymer may be any of a dispersion, a solution, or a mixture thereof.
[0038] The same applies to the mixed solution, which refers to a liquid containing unsubstituted cellulose and a polymer, which exhibits fluidity and solidifies in a state in which the unsubstituted cellulose and the polymer are compatible when the mixed solution comes into contact with a coagulation solvent, and whether the unsubstituted cellulose molecules and the polymer molecules are dispersed in the mixed solution, whether some association remains, or whether fine fibrous materials are merely dispersed (sometimes called a dispersion). That is, in the method for producing porous cellulose of the present disclosure, the mixed solution means a liquid containing unsubstituted cellulose and a polymer, and is a concept that includes a dispersion in which unsubstituted cellulose or a polymer is dispersed in a liquid and a solution in which unsubstituted cellulose or a polymer is dissolved in a liquid. In the method for producing porous cellulose of the present disclosure, the form of the unsubstituted cellulose and the polymer in the mixed solution may be either dispersed, dissolved, or a mixture thereof.
[0039] Hereinafter, the method for preparing a cellulose solution will be specifically described, taking as an example a case where the solvent is an aqueous urea-alkali hydroxide solution. A polymer solution can also be prepared in the same manner, using a polymer as a solute. Also, in a method in which a polymer and an unsubstituted cellulose are dissolved in a solvent simultaneously or sequentially to prepare a mixed solution, a mixed solution can be prepared in the same manner, using unsubstituted cellulose and a polymer as solutes.
[0040] The alkali contained in the aqueous alkali hydroxide solution is preferably lithium hydroxide, sodium hydroxide, potassium hydroxide or quaternary ammonium hydroxide, with sodium hydroxide being most preferred from the standpoints of product safety, cost and ease of solubility or dispersion.
[0041] The alkali concentration of the aqueous alkali solution is not particularly limited, but is preferably 3 to 20% by mass. This range of alkali concentration is preferable because it increases the dispersibility, swelling property, and solubility of the unsubstituted cellulose in the aqueous alkali solution. The alkali concentration is more preferably 5 to 15% by mass, and even more preferably 6 to 10% by mass.
[0042] Urea or thiourea is further added to the above-mentioned alkaline aqueous solution. The concentration of urea or thiourea is preferably 10 to 15% by mass. The three components (cellulose, alkali hydroxide, urea or thiourea) are added to water, and the order of addition is appropriately selected to optimize the dissolution state of cellulose. By cooling the slurry thus obtained under the conditions described later, a non-substituted cellulose solution that is more transparent than immediately after the addition of all the components is obtained.
[0043] As described above, it is preferable that the degree of polymerization of the unsubstituted cellulose is 1000 or less, since the dispersibility and swelling property in an alkaline aqueous solution are high. Another example of the unsubstituted cellulose with improved solubility is dissolving pulp.
[0044] The mixing conditions of the alkaline aqueous solution and the unsubstituted cellulose are not particularly limited as long as an unsubstituted cellulose solution is obtained. For example, the unsubstituted cellulose may be added to the alkaline aqueous solution, or the alkaline aqueous solution may be added to the unsubstituted cellulose. When preparing a polymer solution, the mixing conditions of the alkaline aqueous solution and the polymer are not particularly limited as long as a polymer solution is obtained, and the polymer may be added to the alkaline aqueous solution, or the alkaline aqueous solution may be added to the polymer. In the method of simultaneously or sequentially dissolving the polymer and the unsubstituted cellulose in a solvent to prepare a mixed solution, the mixing order of the polymer, the unsubstituted cellulose, and the solvent is not particularly limited.
[0045] The unsubstituted cellulose may be suspended in water before being mixed with the aqueous alkali solution.
[0046] The concentration of the unsubstituted cellulose in the unsubstituted cellulose solution is not particularly limited as long as it has the fluidity required for the subsequent process and is appropriately set so that the solid content of the porous cellulose prepared from the mixed solution described below is 10% or less, and may be, for example, about 2 to 10% by mass. The concentration of the polymer in the polymer solution is also not particularly limited as long as it is appropriately set so that the solid content and polymer content of the porous cellulose prepared from the mixed solution described below are appropriate, and may be, for example, about 2 to 10% by mass.
[0047] The temperature at which the unsubstituted cellulose solution is prepared is not particularly limited, but for example, the unsubstituted cellulose solution is suitably prepared by mixing the unsubstituted cellulose with an aqueous alkali solution containing urea or thiourea at room temperature, cooling to a low temperature while stirring, and then returning to a temperature that is easy to handle. The temperature at which the unsubstituted cellulose solution is cooled to a low temperature is, for example, 0°C to -20°C, preferably about -5°C to -15°C. The same applies to the temperature at which the polymer solution is prepared.
[0048] A mixed solution is prepared by mixing the unsubstituted cellulose solution and the polymer solution. The mixing ratio of the unsubstituted cellulose solution and the polymer solution is appropriately adjusted so that the polymer content of the porous cellulose prepared from the mixed solution is an appropriate value. When the unsubstituted cellulose solution and the polymer solution are mixed, it is preferable to thoroughly stir the unsubstituted cellulose solution and the polymer solution so that they are mixed to form a one-phase mixed solution. In addition, as described above, the polymer and the unsubstituted cellulose can be simultaneously or sequentially dissolved in a solvent to prepare a mixed solution.
[0049] In the mixed solution, the polymer content is 30% by mass or less out of a total of 100% by mass of the polymer and unsubstituted cellulose. By setting the polymer content to 20% by mass in the mixed solution, it is possible to obtain porous cellulose that exhibits gel properties in water while retaining the porosity formed by the unsubstituted cellulose, and furthermore, that exhibits functionality not found in porous cellulose composed only of unsubstituted cellulose, with the polymer being retained in the porous cellulose. From the viewpoint of more suitably exerting these properties, the content of the polymer in the mixed solution is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less; the lower limit is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more; preferred ranges include about 1 to 20% by mass, about 1 to 15% by mass, about 1 to 10% by mass, about 1 to 8% by mass, about 2 to 20% by mass, about 2 to 15% by mass, about 2 to 10% by mass, about 2 to 8% by mass, about 3 to 20% by mass, about 3 to 15% by mass, about 3 to 10% by mass, and about 3 to 8% by mass.
[0050] The total concentration of the polymer and unsubstituted cellulose in the mixed solution is preferably 1 to 10% by mass. If it is 1% by mass or more, the mechanical strength of the resulting porous cellulose is increased, which is preferable, and if it is 10% by mass or less, the viscosity of the mixed solution is low, which makes it easy to spray from a spray nozzle so as to obtain the above-mentioned predetermined particle diameter, for example. The total concentration of these in the mixed solution is more preferably 2 to 6% by mass, and even more preferably 3 to 5% by mass. Note that this total concentration in the mixed solution does not include components that are not completely dissolved, dispersed, or swollen and are not uniform.
[0051] (solidification process) In the method for producing porous cellulose according to the present disclosure, after the mixed solution preparation step, a coagulation step is performed in which the mixed solution is brought into contact with a coagulation solvent. By bringing the mixed solution into contact with the coagulation solvent, the unsubstituted cellulose solution and the polymer in the mixed solution are coagulated in a compatible state to obtain porous cellulose.
[0052] The specific mode of contact with the coagulation solvent referred to here can be a known method depending on the desired shape of the porous cellulose (for example, particles (spherical particles, irregular particles), lumps (monolith), membrane-like). One of the important shapes in terms of the applications of porous cellulose is spherical particles. In the coagulation step, a representative method for obtaining spherical particles of porous cellulose is to stir and disperse the mixed solution, if necessary together with an appropriate dispersant, in a liquid (for example, liquid paraffin or fluorolube) that has a relatively high viscosity and is immiscible with the mixed solution, and then add the obtained dispersion and the coagulation solvent (a solvent that causes the unsubstituted cellulose and polymer to precipitate when mixed with the dispersion) while stirring.
[0053] It is also possible to make the mixed solution into droplets in a gas using a spray or nozzle, and then drop these into a coagulation solvent. That is, when preparing porous cellulose particles by this method, the coagulation step can be a step of making the mixed solution into minute droplets in a gas, and then absorbing the minute droplets into a coagulation solvent. It is also possible to extrude the mixed solution into a filament, put it into a coagulation solvent, coagulate it, and then cut or crush it into amorphous particles.
[0054] On the other hand, in the coagulation step, when preparing a porous cellulose monolith, the mixed solution is placed in a suitable container and immersed in the coagulation solvent. If possible, the mixed solution can be passed through a gas phase before immersion to absorb the vapor of the coagulation solvent.
[0055] The most common method for obtaining a porous cellulose membrane is to cast the mixed solution onto an appropriate flat plate (a liquid phase of a uniform thickness is formed using a spin coater or bar coater) and then immerse the plate in a coagulation solvent. In order to increase the permeability of the porous cellulose membrane, an additional operation such as absorbing the coagulation solvent from the gas phase before immersion can be performed. When the porous cellulose membrane is in the form of a hollow fiber, the coagulation solvent is passed inside the double tube and the cellulose solution is passed outside, and the outside passes through the gas phase as necessary and then is led into the coagulation solvent (not necessarily the same as that passed through the inner tube).
[0056] The coagulation solvent is not particularly limited as long as it can precipitate the unsubstituted cellulose and the polymer from the mixed solution, and examples of the coagulation solvent include organic solvents such as methanol, ethanol, and acetone; water; water in which a salt such as table salt has been dissolved; and, in the case where the mixed solution contains an alkali hydroxide, water containing an acid.
[0057] For long-term storage in a wet environment, preservatives such as alcohol and sodium azide can be added to prevent decay. Also, the product can be dried, preferably freeze-dried, after adding glycerin, sugar, urea, etc. EXAMPLES
[0058] The present disclosure will be described in detail below with reference to examples and comparative examples. However, each configuration and their combinations in each example are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate within the scope of the gist of the present disclosure. The present disclosure is not limited by the examples, but is limited only by the scope of the claims.
[0059] <Example 1> (Preparation of Unsubstituted Cellulose Solution) In a flask, 70.35 g of sodium hydroxide was dissolved in 808.05 g of water, cooled to room temperature, and 42.11 g of powdered cellulose (unsubstituted cellulose Asahi Kasei Ceolas PH101) was dispersed therein while stirring. 120.05 g of urea was further added and dissolved, and then cooled to -15°C for about 1 hour while stirring, and then warmed to room temperature using a water bath to form an almost transparent solution. Since the water content of the powdered cellulose was 4.25% by mass, the total solvent system was 1000.24 g, the unsubstituted cellulose was 40.32 g, the external unsubstituted cellulose concentration was 4.0% by mass, and the internal unsubstituted cellulose concentration was 3.85% by mass.
[0060] (Preparation of CMC solution) Similarly, when 3.57 g of sodium hydroxide was dissolved in 41.5 g of water, the solution was returned to room temperature, and 0.52 g of carboxymethylcellulose (CMC) (CMC1190, Daicel Corporation) was added, a slightly cloudy, transparent, viscous solution was obtained. When 5.97 g of urea was dissolved in this solution, it became a very transparent solution.
[0061] (Preparation of mixed solution) When 69.90 g of the CMC solution was added to 336.1 g of the unsubstituted cellulose solution and stirred, the mixture was homogeneously mixed to form a transparent mixed solution.
[0062] (Atomization) The resulting mixed solution was sprayed into a mist and absorbed into methanol to obtain a fine powder. This was repeatedly washed with water to obtain porous cellulose, which is a mixture of cellulose and CMC, in pure water.
[0063] (Measurement of CMC content) The porous cellulose obtained in Example 1 and the CMC as a reference were washed with 1N hydrochloric acid to convert the -CO2Na group to the -CO2H group, and then dried. The porous cellulose itself and the CMC as a reference, together with 19 times the amount of unsubstituted cellulose, were ground with potassium bromide, compressed into disks, and the infrared absorption spectrum was measured in the absorption mode. The carboxyl group content was measured using the peak at 2890 cm -1 (νC-H region based on cellulose skeleton) at 1735 cm -1 The relative intensity of the νC=O region (based on the carboxyl group) was calculated. Note that the former was calculated at 3000 cm -1 and 2600cm -1 Nearby, the latter is 1800cm -1 and 1570cm -1 Tangent lines were drawn near the peaks, and these were considered to be the baseline. When the absorbance difference from the baseline to the peak top was taken as intensity I, I for porous cellulose was 1735 / I 2890was 0.204, and that of the reference was 0.17. The acid-type CMC content of the standard sample (wt% of acid-type CMC in the mixture of unsubstituted cellulose and acid-type CMC) was 4.45%, so the acid-type CMC content of the porous cellulose was calculated to be 5.3 wt% (4.45 x 0.204 / 0.17 = 0.053). On the other hand, the CMC content of the solution used to prepare the porous cellulose was calculated to be 4.7 wt% by converting the weight of CMC (normally 1.5 substitution degree, about half of which is Na salt) to the weight of acid-type CMC. Taking into account the measurement accuracy, it can be concluded that almost the entire amount of CMC added remains in the porous cellulose.
[0064] (Measurement of solid content) The solid content of the water-containing porous cellulose particles obtained in Example 1 was measured by the following method, and the solid content was 4.3% by mass. The porous cellulose particles in the state of settling in the pure water were left to stand for one day in an environment at atmospheric pressure and at a temperature of 25°C. Next, about 2 mL of the porous cellulose particles in the pure water were sucked up with a pipette, dispersed in 20 mL of a solution in which a neutral detergent (trade name Mama Lemon, manufactured by Lion Corporation) was diluted 1000 times with pure water, and left to stand for one day to allow the particles to settle. Thereafter, the supernatant was removed by decantation, and 1 / 3 of the remaining slurry was dropped onto a filter paper (No. 131 150 mm manufactured by ADVANTEC Co., Ltd.) equivalent to the three types specified in JIS P 3801 [filter paper (for chemical analysis)] as one sample, and left for 20 seconds to remove excess moisture, and then the mass of the porous cellulose particles remaining on the filter paper was peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose particles. Next, the porous cellulose particles were dried in an oven at 80° C. for 2 hours to obtain the dry mass. These operations were performed for three samples, and the ratio of the dry mass to the wet mass was calculated for each sample. The average of the three values obtained was taken as the solid content.
[0065] Test Example 1 (Adsorption by Porous Cellulose) The porous cellulose obtained in Example 1 was classified with a sieve to obtain a fraction of 53 μm to 106 μm. About 1 mL of the precipitate that had settled in water was placed in a plastic syringe (5 mL) with a filter placed on the bottom, and some water was added and stirred, and the water was allowed to fall naturally from the bottom to create a bed with a depth of 1.4 cm. 4 mL of an approximately 0.2% aqueous solution of potassium carbonate was poured into this bed, and then it was washed twice with 3 mL of pure water. When 2.0 mL of a 3.5 mg / 100 mL solution of methylene blue was passed through this bed, the area 1 to 2 mm deep from the top surface of the bed was colored dark blue. This result indicates that the anionic porous cellulose adsorbs a large amount of cationic methylene blue by ion exchange.
[0066] On the other hand, when the adsorption of methylene blue was confirmed for porous cellulose microparticles prepared in the same manner but without adding CMC, it was found that the surface was colored blue up to a depth of 1 cm from the top, indicating that almost no methylene blue was adsorbed.
[0067] <Example 2> (Preparation of cellulose phosphate solution) 1.00g of Whatman's phosphate cellulose (P11 Phosphorylated Cellulose) was suspended in 14.81g of water, to which was added a solution of 1.75g of sodium hydroxide dissolved in 5.59g of water, and the mixture was thoroughly stirred. After that, 3.0g of urea was added and stirred, which increased the transparency and viscosity of the liquid, resulting in a suspension of swollen insoluble particles. This was cooled in a dry ice bath until some white crystals precipitated, and the stirring was repeated twice while returning to room temperature. This liquid was centrifuged at 10,000 rpm, 4℃, for 15 minutes, and a transparent, viscous supernatant solution was obtained by decantation.
[0068] (Preparation of mixed solution) 90 g of the unsubstituted cellulose solution prepared in the same manner as in Example 1 was mixed with 10 g of the above cellulose phosphate solution and stirred, resulting in a homogeneous mixture that became a transparent mixed solution.
[0069] (Atomization) The resulting mixed solution was sprayed to form a mist and absorbed in methanol to obtain a fine powder in suspension. Acetic acid was added to neutralize the methanol solution, and the fine powder was filtered and repeatedly washed with water to obtain porous cellulose in pure water, which is a mixture of unsubstituted cellulose and cellulose phosphate.
[0070] (Phosphorus Analysis) The resulting particles were dried and subjected to ICP emission analysis, revealing a phosphorus content of 4300 ppm. From this value, the weight ratio of P11 in the dried mixture of cellulose and P11 (cellulose phosphate) is estimated to be 4.6%. The calculation is explained below. According to Whatman's "CERTIFICATE OF ANALYSIS," P11 contains 3.9% water, and the phosphorus content of the dried product is reported to be 28.9%. This can be converted to phosphorus atom content by multiplying it by 31 / 98 (phosphorus atom weight / phosphoric acid molecular weight), which is 9.14%. The phosphorus content value of 4200 ppm obtained from the analysis of the dried particles can be converted to dry P11 content by dividing it by 0.0914 to 0.046, or 4.6%.
[0071] (Measurement of solid content) When the solid content of the hydrous porous cellulose particles obtained in Example 2 was measured in the same manner as in Example 1, the solid content was 4.2% by mass.
Claims
1. Unsubstituted cellulose; A blend polymer having a glucose unit other than the unsubstituted cellulose; A porous cellulose comprising: The content of the polymer is 1% by mass or more and 20% by mass or less in a total of 100% by mass of the polymer and unsubstituted cellulose, The degree of polymerization of the unsubstituted cellulose is 10 or more and 1,000 or less.
2. The porous cellulose according to claim 1, wherein the solid content of the porous cellulose in a water-containing state, as measured by the following method, is 10 mass% or less. (Method of measuring solid content) The porous cellulose in the state of settling in the pure water is left to stand for one day or more in an environment at atmospheric pressure and at a temperature of 25°C. Next, about 2 mL of the porous cellulose in the pure water is sucked up with a pipette, dispersed in 20 ml of a solution in which a neutral detergent is diluted 1000 times with pure water, and left to stand for one day or more to allow the porous cellulose to settle. Then, the supernatant is removed by decanting, and about 1 / 3 of the remaining slurry is dropped onto a filter paper corresponding to the three types specified in JIS P 3801 [filter paper (for chemical analysis)] as one sample, and left for 20 seconds to remove excess moisture, and then the mass of the porous cellulose remaining on the filter paper is peeled off from the filter paper and weighed to obtain the wet mass of the porous cellulose. Next, the porous cellulose is dried in an oven at 80°C for two hours and then weighed to obtain the dry mass. These operations are performed on three samples, and the ratio of the dry mass to the wet mass is calculated for each sample, and the average of the three values obtained is obtained as the solid content.
3. The porous cellulose according to claim 1 or 2, wherein the polymer is a cellulose derivative.
4. The cellulose derivative is at least one selected from the group consisting of carboxymethyl cellulose, carboxyethyl cellulose, cellulose phosphate, cellulose sulfate, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, N,N-diethylaminoethyl cellulose and N,N-dimethylaminoethyl cellulose. The porous cellulose according to claim 3.
5. The porous cellulose according to any one of claims 1 to 4, wherein the porous cellulose has a particle, lump or film shape.
6. A step of preparing a mixed solution containing a polymer having a glucose unit other than unsubstituted cellulose and unsubstituted cellulose; contacting the mixed solution with a coagulation solvent; Equipped with In the mixed solution, a content of the polymer is 1% by mass or more and 30% by mass or less based on a total of 100% by mass of the polymer and the unsubstituted cellulose, The method for producing porous cellulose, wherein the degree of polymerization of the unsubstituted cellulose is 10 or more and 1,000 or less.
7. The method for producing porous cellulose according to claim 6 , wherein in the step of preparing the mixed solution, the mixed solution is prepared by dissolving the polymer and the unsubstituted cellulose in a solvent.
8. The method for producing porous cellulose according to claim 7 , wherein in the step of preparing the mixed solution, the polymer and the unsubstituted cellulose are dissolved in the solvent simultaneously or sequentially to prepare the mixed solution.
9. The method for producing porous cellulose according to claim 6 , wherein in the step of preparing the mixed solution, the mixed solution is prepared by mixing the polymer solution and the unsubstituted cellulose solution.
10. The method for producing porous cellulose according to any one of claims 6 to 9, wherein the polymer is a cellulose derivative.
11. The method for producing porous cellulose according to claim 10, wherein the cellulose derivative is at least one selected from the group consisting of carboxymethyl cellulose, carboxyethyl cellulose, cellulose phosphate, cellulose sulfate, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, N,N-diethylaminoethyl cellulose and N,N-dimethylaminoethyl cellulose.
12. The method for producing porous cellulose according to any one of claims 6 to 11, wherein the step of contacting the mixed solution with the coagulation solvent is a step of converting the mixed solution into microdroplets in a gas and then absorbing the microdroplets into the coagulation solvent.
Citation Information
Patent Citations
Preparation of porous particles of both cellulose and cellulose derivative
JP1990235944A
Modified cellulose porous carrier
JP1992091142A
Production of porous cellulose particle
JP1997132601A
Cellulosic particle and preparation of the same
JP1999158202A
Production method of regenerated cellulose spherical particle
JP2013133355A